Entertainment Cost Efficiency Analysis With Data Envelopment Analysis (Dea) And Fuzzy Logic (Flp & C-Iowa) Approach To Sales Level - Dwi Kakung Saputro; Tedjo Sukmono (Procedia of Engineering and Life Science, 2021)
It caused some problems regarding to calculation and measurement of costs which is issued for the level of efficiency desired by the company, namely PT. LLL Surabaya. From the results of measurements and analysis, it shows that system has objective value in “efficient” category. Therefore, the ranking results of regional operating system (DMU3) are the most optimal in terms of sales capacity, which is Rp. 11,745,050,779. It is caused by the impact of providing these costs. Based on the decision-making preferences related to the entertainment costing system, (CI) value is 0.18 for (P1) and 0.03 for (P2). It means that marketing department has more preference for entertainment costing system should be given constantly with the aim that total sales capacity can continue to increase.